PENGARUH LINGKUNGAN KERJA FISIK DAN DISPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MONICA HIJAU LESTARI TANGERANG SELATAN - Putri Nur Fauziah; Desi Prasetiyani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
The purpose of this research is to determine the extent of the influence of Physical Work Environment and Work Discipline on Employee Performance at PT. Monica Hijau Lestari South Tangerang, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling with 80 respondents. Data analysis includes validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient, and hypothesis testing.The results show that the physical work environment has a significant positive effect on employee performance, with the regression equation Y = 17.379 + 0.847X1, a correlation coefficient of 0.583 (moderate), a determination coefficient of 34%, and hypothesis testing showing t-value > t-table (6.332 > 1.664). Work discipline has a significant positive effect on employee performance, with the regression equation Y = 20.089 + 0.871X2, a correlation coefficient of 0.621 (strong), a determination coefficient of 38.5%, and hypothesis testing showing t-value > t-table (6.993 > 1.664).Simultaneously, physical work environment and work discipline have a significant effect on employee performance, with the regression equation Y = 16.283 + 0.391X1 + 0.602X2, a correlation coefficient of 0.637 (strong), a determination coefficient of 40.6%, with the remaining 59.4% influenced by other variables. Hypothesis testing shows F-value > F-table (26.355 > 3.12), indicating that physical work environment and work discipline significantly influence employee performance.